Przekład jako narzędzie propagandy. Miesięcznik „Polska: czasopismo ilustrowane” w latach 1954—1956 / Translation as a propaganda tool The monthly Poland: Illustrated Magazine in the years 1954—1956 - Solová, Regina (Przekłady Literatur Słowiańskich, 2019)
The monthly Poland: Illustrated Magazine was published (with an interruption) from 1954 to 1999. In the period under analysis (1954—1956), apart from its Polish version, the magazine was also published in English, French, Spanish, German, and Russian. The periodical was a product of the export circulation of cultural goods, the aim of which was to export translations of texts published in the country and those specifically intended for foreign readers. The initial task of the monthly was to shape the image of socialist Poland abroad. Through an analysis of texts intended for export, we examine how the monthly was used for propaganda purposes in the years making to the end of Stalinism and the beginning of “the thaw” in Poland.